Recent advances in EAST physics experiments in support of steady-state operation for ITER and CFETR. (5th June 2019) - Wan, B.N.; Liang, Y.; Gong, X.Z.; Xiang, N.; Xu, G.S.; Sun, Y.; Wang, L.; Qian, J.P.; Liu, H.Q.; Zeng, L.; Zhang, L.; Zhang, X.J.; et al.
Abstract: Since the last IAEA Fusion Energy Conference in 2016, the EAST physics experiments have been developed further in support of high-performance steady-state operation for ITER and CFETR. First demonstration of a >100 s time scale long-pulse steady-state scenario with a good plasma performance (H98(y2) 1.1) and a good control of impurity and heat exhaust with the upper tungsten divertor has been achieved on EAST using the pure radio frequency (RF) power heating and current drive. The EAST operational domain has been significantly extended towards a more ITER and CFETR related high beta steady-state regime ( β P 2.5 and β N 1.9 of using RF and NB and β P 1.9 and β N 1.5 of using pure RF). A large bootstrap current fraction up to 47% has been achieved with with q 95 6.0–7.0. The interaction effect between the electron cyclotron resonant heating and two lower hybrid wave systems has been investigated systematically, and applied for the improvement of current drive efficiency and plasma confinement quality in the steady-state scenario development on EAST. Full edge-localized mode (ELM) suppression using the n = 2 resonant magnetic perturbations has been achieved in ITER-like standard type-I ELMy H-mode plasmas with a range of the edge safety factor of q 95 ≈ 3.2–3.7 on EAST. Reduction of the peak heat flux on the divertor was demonstrated using the active radiation feedback control. An increase in the total heating power and improvement of the plasma confinement are expected using a 0D model prediction for a higher bootstrap fraction. Towards a long-pulse, high bootstrap current fraction operation, a new lower ITER-like tungsten divertor with active water-cooling will be installed, together with further increase and improvement of heating and current drive capability.